FATIGUE LIFE PREDICTION METHODOLOGY BASED ON WEIGHT-AVERAGED MAXIMUM SHEAR STRESS PLANE UNDER MULTIAXIAL LOADING - TAO ZhiQiang; ZHANG Ming; ZHU Yu; CHENG Rong; WANG LeiJie; LI Xin (Jixie qiangdu)
A fatigue life prediction methodology is proposed based on weight-averaged maximum shear stress range plane.Firstly,based on modified Wang and Brown’s reversal counting method,a new approach to the determination of the critical plane is proposed under multiaxial variable amplitude loading. For the entire loading history,the orientation angle of the critical plane is determined through averaging the orientation angles of maximum shear stress range planes with largest normal tensile stress in all counted reversals. The weight function is defined as the ratio of maximum shear stress range for every counted reversal to the largest shear stress range for all counted reversals. The accuracy of the proposed critical plane approach is verified using experimental data of 7050-T651 aluminium alloy notched tubular specimens. Then,the proposed determination approach of critical plane is combined with multiaxial high-cycle fatigue criterion and Miner damage rule to establish the fatigue life prediction methodology under multiaxial variable amplitude loading. Finally,the proposed fatigue life prediction methodology is verified by the experimental data of 7050-T651 and 2024-T4 aluminum alloy notched tubular specimens,and the results show that the proposed methodology has good prediction results.